Building a Sustainable Cybersecurity Culture - Zulpratita, Ulil Surtia; Rosita, Ai; Ferry, Sulianta; Rumaisa, Fitrah; Yuliani, Sy.; Laksana, Eka Angga (CENTRAL ASIA AND THE CAUCASUS, 2022)
Cyberattacks are currently the quickest developing wrongdoing on a worldwide scale. Monetary losses from cybercrime surpass the total misfortunes brought about from the worldwide trade of every illegal drugs. Henceforth, it shocks no one that people and associations working on the web live in dread of potential hacking situations and data breaches. Beside monetary misfortunes, such types of digital assaults can prompt standing harm also. Human oversight and cyberattacks are inseparably connected. The most fragile link in cybersecurity is the human factor. As cybercriminals keep on embracing new advancements and assault systems, associations should adjust their way to deal with cybersecurity. A strong security culture not just interfaces with the everyday techniques, yet in addition characterizes what security means for the things that association provides to other people. Those contributions might be products, services, or solutions; however, they should have security applied to all parts and pieces. A sustainable security culture is relentless. It is not a once-a-year occasion, it is behavior, which is however embedded in all that we do.